Pretty Minnie in Paris - Steel, Danielle; Valiant, Kristi (New York : Doubleday, 2014)
In Paris, France, Minnie, a long-haired teacup chihuahua who loves to dress up, gets separated from her fashion-loving owner, Francoise, at a fashion show.
Keywords: Chihuahua (Dog breed) -- Juvenile fiction; Dogs -- Juvenile fiction; Fashion -- Juvenile fiction; Fashion shows -- Juvenile fiction; Chihuahua (Dog breed) -- Fiction; Dogs -- Fiction; Fashion -- Fiction; Fashion shows -- Fiction; Paris (France) -- Juvenile fiction; France -- Juvenile fiction; Paris (France) -- Fiction; France -- Fiction